Breaking Boundaries in Theology : In Conversation with Roger Haight SJ - Telser, Andreas (Religion and Transformation in Contemporary European Society, 2025)
American Jesuit Roger Haight (born 1936) undoubtedly belongs to the circle of Catholic theologians who have set standards across denominational boundaries, particularly in the English-speaking world. Haight's writings have attracted both attention and criticism. The anthology will be the first comprehensive and international examination of central aspects of Haight's theology. A detailed introduction, which primarily aims to situate Haight's theology in his social and cultural context, is followed by three sections that present central aspects of his theology and conversationally develop them. The first section, Finding God within the World, has the clearest fundamental theological contours, echoing Ignatian themes. The following sections focus on Spirituality and on Haight's Christology in connection with his liberation theological concerns. The book includes also an online conversation with Roger Haight. "Like the music of Mozart and Beethoven which he loved, Roger Haight's theology flowed in creative ways while building upon a deep structure. Never without his playlists, earbuds, or tickets to the NY Philharmonic, he radiated curiosity and a centered peace." - Elizabeth Johnson, Distinguished Professor Emerita of Theology, Fordham University, New York City "Roger Haight's theology was simply a reflection of who he was: such a keen mind, so good-humored, ready always to advise 'onward and upward,' and yes, above all, kind." - Leo J. O'Donovan, SJ, President Emeritus, Georgetown University, Washington D.C. "As a teacher, theologian, priest, mentor, and friend, Roger Haight was without peer. His openness, generosity, and incisive clarity - paired with a ready and wry sense of humor - were wellsprings of inspiration and joy for those who studied and worked with him. This book is a wonderful testament to the theology of conversation of Roger Haight." - Lisa Holsberg, Adjunct Professor, Fordham University, New York City